2007
DOI: 10.1387/ijdb.072390fg
|View full text |Cite
|
Sign up to set email alerts
|

The molecular biology of ear development - "Twenty years are nothing"

Abstract: Views of classical biological problems changed dramatically with the rise of molecular biology as a common framework. It was indeed the new language of life sciences. Molecular biology increasingly moved us towards a unified view of developmental genetics as ideas and techniques were imported to vertebrates from other biological systems where genetics was in a more advanced state. The ultimate advance has been the ability to actually perform genetic manipulations in vertebrate organisms that were almost unthin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Neural and sensory cell progenitors in the otic placode during embryonic development (Fekete and Wu, 2002; Barald and Kelley, 2004; Giraldez and Fritzsch, 2007) can produce neurons and hair cells after they are separated and cultured apart from the embryo (Adam et al, 1998), and some reports have indicated that single progenitors can give rise to neurons and sensory epithelial cells in the inner ear (Satoh and Fekete, 2005). Progenitors in the otic placode give rise to all cells in the inner ear except the glial cells in the spiral ganglion, which are thought to be derived from neural crest (Neves et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Neural and sensory cell progenitors in the otic placode during embryonic development (Fekete and Wu, 2002; Barald and Kelley, 2004; Giraldez and Fritzsch, 2007) can produce neurons and hair cells after they are separated and cultured apart from the embryo (Adam et al, 1998), and some reports have indicated that single progenitors can give rise to neurons and sensory epithelial cells in the inner ear (Satoh and Fekete, 2005). Progenitors in the otic placode give rise to all cells in the inner ear except the glial cells in the spiral ganglion, which are thought to be derived from neural crest (Neves et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The external ear is evidently recognizable after Carnegie stage (CS) 16, and its movement has been described in most embryology textbooks as well [1-5]. The external ears are contained in the lower neck region at CS 17.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial phase in development of the sensory structures of the inner ear occurs as the otic epithelium acquires regional identity along its axes. Classic explant experiments by developmental biologists first suggested that otic patterning occurred in response to signals from surrounding tissues, and recent work has revealed much of the molecular basis of these interactions [for review see [ 1 - 3 ]]. For example, genetic studies in the mouse showed that genes expressed along the dorsoventral axis of the otic vesicle are induced by signals from the roof plate and floor plate of the neural tube [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%